Manajemen Penyelenggaraan Program Pendidikan Inklusif di Sekolah Dasar - Dewi Siti Solihah; Nenden Ineu Herawati; Indra Nugrahayu Taufik (Universitas Negeri Padang, 2024)
This research explains the management of implementing inclusive education in elementary schools. A literature study approach was used in this research. As an embodiment of equitable education for both children in general and children with special needs, it is necessary to implement inclusive education programs implemented by schools, especially in elementary schools. The management of inclusive education programs in elementary schools needs to be optimized so that all children can experience education anywhere and for anyone. The role of the school principal as the highest decision-holder in an institution greatly influences the direction and goals that the institution wishes to achieve. From this research, it can be concluded that in the implementation of inclusive education, there are important basic principles, namely the implementation of inclusive education that is friendly, flexible, open, accommodates needs, and is willing to make system changes. By implementing good management of inclusive education programs, especially in elementary schools, it will provide very effective benefits, namely fighting discriminatory attitudes, creating a society that is willing to accept the arrival of extraordinary children, and realizing education for all.